Pengaruh Kualitas Layanan Dan Kualitas Produk Mobile Banking Terhadap Kepuasan Nasabah Pada PT. Bank Syariah Indonesia KCP Bogor Citeureup 3 - Rafin Dwi Purnomo; Taat Kuspriyono (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2024)
With its development, society expects needs, one of which is in the field of financial transactions, one of which is a financial process framework. Advances in information technology in the service sector have been utilized by product marketing and financial institutions, especially Bank Syariah Indonesia. With the launch of sharia banking service information technology known as BSI Mobile. The presence of BSI Mobile makes it easier for every customer to get services and products without having to go to the nearest office. And with BSI Mobile, it is hoped that Bank Syariah Indonesia can achieve customer satisfaction in using it. This research focuses on improving service quality and Mobile Banking product quality on customer satisfaction at PT. Bank Syariah Indonesia KCP Bogor Citeureup 3. The research method used is a quantitative method approach with data collection techniques using accidental sampling or non-probability using the entire population when dealing directly at the BSI Citeureup office 3. The population in question is all customers who have BSI Bank savings, totaling 50 respondents using a questionnaire on a Likert scale. In data processing for analysis using SPSS 25 software with multiple regression analysis techniques with results Y = 8.311, X1 = 0.287, for X2. And simultaneously, the two independent variables get a calculated F of 20.682. In terms of the coefficient of determination, it was found that the two independent variables had an influence of 51.8%. This research shows that there is a positive and significant partial or simultaneous influence between the service quality and product quality variables on customer satisfaction at PT. Bank Syariah Indonesia KCP Bogor Citeureup 3.